2020
DOI: 10.1111/polp.12344
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Competing Effects of Economic Hardship and Income Inequality on Voter Turnout

Abstract: This article examines how economic hardship and income inequality affect voter turnout across 41 elections from 22 countries. Research on how these factors affect voter turnout has routinely produced uneven results. Furthermore, recent rises in income inequality have led many to revisit how the distribution of resources in society may affect voting. Using multilevel modeling techniques, I find strong evidence that economic hardship negatively affects participation rates for those mainly from lower socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The relationship has predominantly been examined cross-nationally at the individual level (Anderson and Beramendi, 2008;Filetti, 2016;Filetti and Janmaat, 2018;Horn, 2011;Jaime-Castillo, 2009;Jensen and Jespersen, 2017;Lancee and Van de Werfhorst, 2012;Persson, 2010;Schäfer and Streeck, 2013;Schäfer and Schwander, 2019;Solt, 2008;Steinbrecher and Seeber, 2011;Wilford, 2020), but also within the US (Solt, 2010;Szewczyk and Crowder-Meyer, 2020). The studies span various time periods and find inequality to predominantly exert either a negative or null relationship.…”
Section: Inequality and Turnout Literaturementioning
confidence: 99%
“…The relationship has predominantly been examined cross-nationally at the individual level (Anderson and Beramendi, 2008;Filetti, 2016;Filetti and Janmaat, 2018;Horn, 2011;Jaime-Castillo, 2009;Jensen and Jespersen, 2017;Lancee and Van de Werfhorst, 2012;Persson, 2010;Schäfer and Streeck, 2013;Schäfer and Schwander, 2019;Solt, 2008;Steinbrecher and Seeber, 2011;Wilford, 2020), but also within the US (Solt, 2010;Szewczyk and Crowder-Meyer, 2020). The studies span various time periods and find inequality to predominantly exert either a negative or null relationship.…”
Section: Inequality and Turnout Literaturementioning
confidence: 99%
“…It has been theorized that children from high-SES families receive more parental political socialization than children from low-SES families (Verba et al 2003(Verba et al , 2005Schlozman et al 2012Schlozman et al , 2018. This is because high-SES parents participate in politics more actively than low-SES parents (Campbell et al 1960;Verba and Nie 1972;Milbrath and Goel 1977;Verba et al 1978Verba et al , 1995Verba et al , 2003Dalton 2017;Quaranta 2018;Wilford 2020). High-SES individuals do so because they have more resources (money, knowledge, social skills) and motivation to participate than low-SES individuals (Brady et al 1995;Verba et al 1995).…”
Section: The Influence Of Parents and Education On Political Particip...mentioning
confidence: 99%
“…Studies have found inequality and turnout to exert either a negative or null relationship, with scant evidence of a positive relationship. Fully two‐thirds of studies find a negative and statistically significant effect (Anderson & Beramendi, 2008; Jaime‐Castillo, 2009: Jensen & Jespersen, 2017; Lancee & Van de Werfhorst, 2012; Macdonald, 2021; Polacko, 2022a; Polacko et al, 2021; Schäfer, 2013; Schäfer & Schwander, 2019; Solt, 2008, 2010; Steinbrecher & Seeber, 2011; Szewczyk & Crowder‐Meyer, 2022; Wilford, 2020) but the absence of any effect or, indeed, a positive effect in the other studies (Fumagalli & Narciso, 2012; Horn, 2011; Persson, 2010; Stockemer & Parent, 2014; Stockemer & Scruggs, 2012), both indicate that the relationship between inequality and turnout is complex. These academics have developed two principal theories attempting to explain the effects of inequality on turnout, namely “power resource” and “conflict” theory.…”
Section: Turnout and Inequalitymentioning
confidence: 99%
“…Voter turnout has been on the decline in many advanced democracies. While scholars point to a range of causes—such as generational value change (Blais & Rubenson, 2013; Kostelka & Blais, 2021), party system convergence (Callander & Wilson, 2007), declining satisfaction with democracy (Foa et al, 2020), and increasing elective institutions (Kostelka & Blais, 2021)—mounting evidence points to rising income inequality as a culprit (Anderson & Beramendi, 2008; Jaime‐Castillo, 2009: Jensen & Jespersen, 2017; Lancee & Van de Werfhorst, 2012; Macdonald, 2021; Polacko, 2022a; Polacko et al, 2021; Schäfer, 2013; Schäfer & Schwander, 2019; Solt, 2008, 2010; Steinbrecher & Seeber, 2011; Szewczyk & Crowder‐Meyer, 2022; Wilford, 2020). Simultaneously, the once‐ascendent social democratic party family has experienced pronounced electoral decline.…”
mentioning
confidence: 99%